Perancangan Aplikasi Pengolah Data Siswa Berbasis Android (Studi Kasus : Mis Nurul Huda Labuhan Batu Selatan) - Ardian, Andre (Journal of Computer Science and Information System(JCoInS), 2021)
The development of technology today, especially information technology is growing increasingly rapidly, as well as the development of mobile technology that presents smartphones with various functions, not just a communication device,but also as a source of information used by society today. Similarly, the development of Information Systems is no exception in the world of Education. Education as a container or place where the educational process takes place in conjunction with the process of culture still has many problems in inputting data, data storage and most importantly in the search for student data. One of the problems in the search for student data, because they have to check from some of the existing files on the administration desktop which are arranged in too many files, thereby slowing down the work of the administration in searching for student data, and more fatal again the school loses and damages data due to virus attacks that can harm students or the school. . The data collection method used is by FIELD study that is observation (observation), interview (interview), and library study. The programming used is Android programming using MySQL and PHP databases. This study resulted in the design of an android-based student data processing application for MIS NuruL Huda Labuhanbatu Selatan. Hopefully with this application can improve the work process of the teacher council or administrative staff in processing student data more easily.